Obtenção de extratos e frações de folhas de uma nova variedade de stevia rebaudiana, forticação da atividade antioxidante e antidiabética de whey protein isolado com fração de stevia rica em compostos fenólicos - Milani-Fernandes, Paula Gimenez (2017)
Stevia rebaudiana (Bert.). Bertoni is worldwide known and explored by presenting high sweetener power steviol glycosides naturally in its leaves. Among these compounds, the most prominent ones are the stevioside and the rebaudioside A, both have been studied in the last decades also by their antidiabetic properties. However, besides the steviol glycosides, the stevia leaves have been described as phenolic and flavonoids compounds source, with antioxidant and antidiabetic source. Many efforts have been made directed to isolating and characterizing fractions rich in phenolic compounds from stevia leaves of a new seminal and elite variety, Stevia UEM-13, with the purpose of evaluating their potential of use as multi-functional source of phenolic compounds. This study relates the obtainment of a stevia fraction with high phenolic compounds content, which had its centesimal composition determined and also, its main present phenolic and flavonoids were identified, through LCMS analysis. The fraction with potential for fortifying foods was added in a protein isolate obtained from whey (WPI), and the developed supplement was tested for its antioxidant potential and antidiabetic effects.The objective of this study was to determine the composition and antioxidant potential of leaves of a new seminal variety of Stevia rebaudiana (Stevia UEM-13), to determine the levels of steviol glycosides, phenolic compounds, flavonoids and antioxidant capacity of different extracts and fractions obtained from the leaves of Stevia UEM-13 and to evaluate the potential of the fraction with high antioxidant capacity, obtained by fractionation with ethyl acetate, as a fortifier of the antioxidant and antidiabetic activity of whey protein isolate produced by membrane separation processes.The plants of Stevia rebaudiana of the seminal variety UEM 13 grown at NEPRON (UEM) were collected at maximum vegetative growth stage. These shrubs were previously dried in an oven at 60°C and the leaves were subsequently separated from the stems and branches, placed in polyethylene bags, and stored at -18°C before developing different extracts. The chemical reagents were purchased from Sigma-Aldrich. Different extracts and fractions were obtained from these leaves and were analyzed for total glycosides (HPLC), phenolic compounds (Folin) and total flavonoids and antioxidant capacity (DPPH). Aqueous extract of Stevia leaves UEM-13 was obtained by means of an aqueous extraction of a sample of 2.0 g of leaves, added with 250 ml of distilled water and heated to 100 ºC. Samples from the same sheet were also used for extractions with the solvents absolute ethanol and methanol, which were used for extraction in Sohxlet apparatus and maceration (absolute ethanol only). The methanolic extract, due to the higher extraction yield of the compounds of interest, was fractionated with hexane, chloroform, ethyl acetate and isobutanol and the fractions obtained were analyzed. The ethyl acetate fraction (ASF), because it was free of glycosides and with high antioxidant capacity, was analyzed in LCMS/MS and the phenolic and flavonoid compounds were identified, and in addition its proximal composition was determined. ASF was used as a fortifying fraction of a whey protein isolate (ASF was added at 0.2% concentration to the WPI). The WPI obtaining was made in accordance to Milani et al. (2016) with modifications. The whey was concentrated in ultrafiltration system (UF), diafiltration (DF) and (NF). A sample of this concentrated was dried in spray dryer. The UF and DF processes were made in a system with polyethersulfone filtering membranes (10 kD cut off), Koch brand, in spiral configuration, with 50 cm2 area. 12 diafiltration cycles were performed. The nanofiltration was performed in reverse osmosis system, composed by two polyamide membranes with 180D cut off molecular mass (Koch) and 500D (Millipore), both in spiral configuration, with 50 cm2 area each one. The WPI drying was made in a spray dryer atomizer. The MTT test was made in adipose cells to evaluate the ASF fraction cytotoxicity. To test the antidiabetic activity, 4 experimental groups were established, receiving the following supplements daily: 1) WPI - whey protein isolate (100 mg/kg); 2) ASF - stevia fraction (0.2 mg/kg); 3) WPI+ASF - protein isolate of whey fortified with 0.2% of the stevia fraction (100mg/kg); 4) DC- diabetic control; Received only water and feed. A fifth group (C) non-diabetic and non-supplemented was also established. The oral supplementation was performed daily, at 08:00 AM, for a 30 days period, by gavage (the control diabetic animals group received pure water). Fasting and fed blood glucose and body weight were evaluated weekly. After the treatments were evaluated plasma and serum levels of glucose, total cholesterol, HDL cholesterol, triglycerides, fructosamine, AST and ALT. The total antioxidant capacity was also evaluated in the plasma of all groups of animals after treatment. Among the main results of the different extractions made from the Stevia UEM-13 leaves, we can highlight that the methanolic extract presented higher extraction yield of the compounds of interest when compared to the ethanolic extract and therefore it was fractionated with different solvents. The isobotanolic fraction showed a higher content of glycosides (65.3%). The fraction obtained in ethyl acetate presented the highest content of phenolic compounds and flavonoids (524.20 mg galic acid equivalent/g; 380.62 μg quercetin equivalent/g respectively), and also of antioxidant capacity and presented with low glycosides content. the main identified by LC-MS were caffeic acid, quercetin-3-o-glycoside, cyanidin-3-glucoside, kaempferol, quercetin, apigenin, rozmarinic acid, clhologenic acid e dicaffeoylquinic acid. The stevia fraction in ethyl acetate (ASF) was used as a multi-functional source of phenolic compounds in the fortification of the whey protein isolate (WPI) obtained by membranes separation processes. WPI fortified with 0.2% of ASF had its antioxidant activity increased in 80%. WPI fortified with ASF presented more pronounced antidiabetic effects in relation to the WPI unfortified, mainly in the glycemic control of diabetic animals induced by streptozotocin. In vitro and in vivo antioxidant effects found important in stevia fraction, what contributed in an expressive way for fortifying the WPI. This pioneer study shows that the ASF can be used for enriching the WPI antioxidant and antidiabetic properties. The evaluation of extraction and fractionation of this plant using different solvents and methodologies resulted in extracts of different antioxidant capacity, which can be used to enrich the literature and contribute to their application in foods, pharmaceuticals and cosmetics. A diet rich in antioxidants may contribute significantly to prevent degenerative diseases, cardiovascular and metabolic diseases, such as diabetes mellitus. Thus, natural and industrialized foods enriched with flavonoids and phenolic compounds contribute to the reduction of these diseases. The present study showed that ethanol, methanol and ethyl acetate extracts of Stevia rebaudiana leaves (Stevia UEM-13) have a great potential antioxidant and so can be used as possible additives to enhance the functionality of food and beverages. Through membranes separation processes it was possible to obtain from whey the whey proteins isolate (WPI), which had its centesimal composition determined; The stevia fraction, obtained from Stevia UEM 13 variety leaves, with 3.82% yield, exhibited phenolic compounds as main constituents. The main identified phenolic acids and flavonoids in the ASF comply with the data literature. The ASF in the 0.2% concentration promoted increase of 80% in the WPI antioxidant activity. The physiological tests showed that the three supplements (ASF, WPI and WPI+ASF) were beneficial for improving the metabolic control of diabetic mice. The WPI fortified with ASF was the food supplement with expressive functionality, showing that the ASF has potential to be used as a fortifier or an antioxidant and antidiabetic activity enriching of foods or supplements.